Long-term cycling of 137Cs in Pinus Kesiya at Wat Chan Thailand. (August 2019) - Itthipoonthanakorn, T; Shaw, G
Abstract: Surface soil and above-ground parts of Pinus kesiya (Three-needled pine) were collected at Wat Chan pine forest to study cycling of 137 Cs. Cs-137 derived from nuclear weapons tests up to 1963 was found to have accumulated at a shallow depth (<5 cm) in the forest soil. Calculated total deposition of 137 Cs was in the range of previous studies and could be used as a reference for nuclear test deposition of 137 Cs fallout in northern Thailand and nearby locations. Potassium in soil does not appear to be a good indicator for long-term radiocaesium cycling. Finally, 'available' stable caesium ( 133 Cs) in the soil was found to be an appropriate indicator for studying uptake of 137 Cs by Pinus kesiya at Wat Chan.